Numerical simulation of a mesoscale convective complex: model development and numerical results - Tremback, Craig J., author (Colorado State University. Libraries, 1990)
A mesoscale numerical model has been developed and used to study the complex circulations of a baroclinic environment which supported the development of a mesoscale convective complex (MCC). The hydrostatic numerical model was first written as a separate version of the CSU cloud/mesoscale model. The non-hydrostatic cloud model and the hydrostatic meso-/synoptic-scale model were combined in 1983 to form the CSU Regional Atmospheric Modelling System (RAMS). Some of the aspects of RAMS developed during the coarse of this research were a hydrostatic "time-split" time differencing scheme, a prognostic soil temperature and moisture model, a new form of the higher ordered forward upstream advection scheme, an improved version of the Fritsch and Chappell convective parameterization scheme, a simple form of the Kuo-type convective parameterization scheme, and an isentropic data analysis package. The goal of the numerical simulations was to employ the numerical model to study an MCC with higher space an time resolution than is available through observational means, not to reproduce the observations that were available. The model results were compared with the observations, however, to examine the credibility of the model. While there were many differences, the coarse resolution (about 110 m) control run simulated an MCC whose mesa-a-scale structure and environment evolved similarly with the observed convective system to establish the credibility of the numerical model. Two additional coarse resolution simulations were used to exam5ne the predictability of the model formulation and sensitivity to initial conditions These simulations showed more research still needs to be done on basic modelling problems in order to apply these models to operational forecasting. Higher resolution simulations (about 45 km) were ma.de to increase the spatial resolution. A comparison between the coarse resolution and higher resolution runs showed only small differences in the gross behavior of the simulated MCC disturbance. The results of the higher resolution control run were examined for the important forcing mechanisms of this MCC. For the development of the MCC, an important forcing mechanism was the development and propagation of the mountain/plains solenoidal circulation which was forced by the baroclinicity created by the physiographic features of the topography slope and horizontal gradients of soil moisture. Other factors present in the simulation that were hypothesized to be important were a low-level "heat low" in the Montana-Wyoming region, the Bermuda high providing a favorable pressure gradient over the central plains for the development of a strong nocturnal low-level jet, a weak front moving southward from Canada, and an upper level jet core in a favorable position to provide upper-level divergence. Results from a two-dimensional simulation, in which a simplified physiographic forcing was used to create a solenoid, verified many features of the solenoid's behavior. The solenoid may also be responsible for the nocturnal preference for MCCs and the frequently observed mid-level shortwave that often accompanies the convective systems. Two higher resolution sensitivity simulations were performed. The first, in which the convective parameterization was not used, showed the expected result that no mesoscale circulations developed that exhibited the characteristics of an MCC. This dry run, as with the control run, produced a low-level solenoidal circulation which propagated across the Dakotas. At the end of the simulation, the dry solenoid looked very similar to the solenoid in the control run after the MCC disturbance outran the solenoid. The second sensitivity experiment with the resolved microphysical parameterizations activated showed that the gross behavior of the MCC was similar to the control run although there were differences in the details of the mesoscale vertical motion fields and locations of convection underneath the anvil.
Spring 1990.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1990.
Keywords: Mesometeorology; Convection (Meteorology); Convective clouds; Numerical weather forecasting